Mining and campesino engagement: an opportunity for integrated water resources management in Ancash, Peru. Issue 3 (15th April 2016) - Patrick, Robert; Bharadwaj, Lalita
ABSTRACT: Mining has become Peru's largest source of revenue. There is evidence that many of the economic and social benefits of this burgeoning industry are not evenly shared across society. Uncertainty over water quality impacts from recent mining activity has been raised by indigenous campesino (peasant) communities in the Ancash Region highlands of central Peru. Adding to the growing conflict amongst competing water users is the current reduction of water availability caused by regional glacial recession. Based on interviews and focus groups this article explores opportunities for integrated water resources management to improve opportunities for campesino engagement in water resources decision making.